Ripple Effects Mapping for Extension Program Evaluation - Kelly Wilson; Ramona Madhosingh-Hector; Linda Seals; David Outerbridge; John Diaz; Paul Monaghan (EDIS)
This publication introduces Extension agents to Ripple Effects Mapping (REM), encourages them to continue exploring the methodology, and promotes collaboration with agents currently using it to learn more about ways to apply it to their own work. This guide explains the four key components of REM, describes the steps to conduct REM for Extension program evaluation, and demonstrates a real-life example of the use of REM in an Extension program. Written by Kelly Wilson, Ramona Madhosingh-Hector, Linda Seals, David Outerbridge, John Diaz, and Paul Monaghan, and published by the UF/IFAS Department of Agricultural Education and Communication, April 2025.